Investigative Reporting in the Digital Era (Films Media Group, 2014)
In the new world of tweets, blogs, and citizen journalism, what is the outlook for true investigative reporting? This program highlights the ways investigative journalism is changing, particularly in the context of digital and online media. Social media and globalization have changed the ways reporters connect with their readers. What are the advantages and disadvantages of nearly instantaneous access to news as it unfolds? A panel of heavy hitters from the world of journalism weighs in on these and other issues, such as emerging financial models for (costly) investigative reporting as traditional news budgets shrink. Young reporters entering the field will be particularly encouraged by many of the exciting technologies and resources available for developing stories that are more in-depth, media-rich, and engaging. Investigative journalism is a fast-evolving field, and this program helps entry-level reporters as well as veterans to bear witness more effectively in the Internet era.